PEMANFAATAN PERPUSTAKAAN SEKOLAH DI SD MUHAMMADIYAH WIROBRAJAN 3 YOGYAKARTA - Abue Dzar Algifarie; Suyatno Suyatno (Universitas Ahmad Dahlan, 2019)
ABSTRACT This study aims to describe the use of libraries in Muhammadiyah Wirobrajan 3 Elementary School Yogyakarta, including the presence of students in the library, student activities in the library, book collections in the library and services in the library. This study included qualitative descriptive research. Research subjects of principals, librarians, teachers and students. The object of this research is the use of school libraries. The validity of the data in this study uses data source triangulation and technique triangulation. The technique of collecting data through interviews, observation and documentation. The data analysis technique uses the Miles and Hubermen models which include data collection, data reduction, data presentation and conclusion drawing. The results showed that the library at SD Muhammadiyah Wirobrajan 3 Yogyakarta in its utilization was very good. The use of the library is realized so that the library becomes the most important part of its existence in the school environment. In the use of libraries in SD Muhammadiyah Wirobrajan 3 Yogyakarta is seen from a complete collection of books, high numbers of student visits to libraries, utilization of library space for activities in teaching and learning processes, libraries are comfortable places for students to do assignments and libraries are a solution for students to borrow books when needing references when learning is taking place. In the use of the library, students are also helped by a good library service. Keywords: Library use, SD Muhammadiyah Wirobrajan ABSTRAK Penelitian ini bertujuan mendeskripsikan pemanfaatan perpustakaan di SD Muhammadiyah Wirobrajan 3 Yogyakarta, meliputi kehadiran siswa di perpustakaan, Aktfitas siswa di perpustakaan, koleksi buku di perpustakaan dan pelayanan di perpustakaan. Penelitian ini termasuk penelitian deskriptif kualitatif. Subjek penelitian kepala sekolah, petugas perpustakaan, guru dan siswa. Objek penelitian ini adalah pemanfaatan perpustakaan sekolah. Keabsahan data dalam penelitian ini menggunakan trianggulasi sumber data dan trianggulasi teknik. Teknik pengumpulan data melalui wawancara, observasi dan dokumentasi. Teknik analisis data menggunakan model Miles dan Hubermen yang meliputi pengumpulan data, reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa perpustakaan di SD Muhammadiyah Wirobrajan 3 Yogyakarta dalam pemanfaatannya sangat baik. Pemanfaatan perpustakaan diwujudkan agar perpustakaan menjadi bagian terpenting keberadaannya dalam lingkungan sekolah. Dalam Pemanfaatan perpustakaan di SD Muhammadiyah Wirobrajan 3 Yogyakarata dilihat dari koleksi buku yang lengkap, tingginya angka kunjungan siswa ke perpustakaan, pemanfaatan ruang perpustakaan untuk kegiatan proses belajar mengajar, perpustakaan menjadi tempat yang nyaman bagi siswa untuk mengerjakan tugas dan perpustakaan menjadi solusi bagi siswa untuk meminjam buku ketika membutuhkan referensi ketika pembelajaran sedang berangsung. Dalam pemanfaatan perpustakaan, siswa juga terbantu dengan pelayaan perpustakaan yang baik.Kata kunci: Pemanfaatan perpustakaan, SD Muhammadiyah Wirobrajan.